Competing for sustainability? An institutionalist analysis of the new development model of the European Union - Claudius Gräbner-Radkowitsch; Theresa Hager; Anna Hornykewycz (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2022)
This paper explores whether the EU's new economic development model of 'competitive sustainability' could serve as a role model for ecologically sustaina-ble development models for advanced economies in general. To this end, we first discuss theoretically the interplay between 'competitiveness' and 'sustaina-bility' and identify several challenges for combining them. In delineating different interpretations of competitive sustainability, we emphasize that operationalizing the concept requires deliberate design of the institutions governing competition so that it can contribute to sustainability. We substantiate our claim by using in-put-output data to analyze whether the identified challenges are indeed relevant. We conclude that they are, and finally propose possible solutions.
Keywords: B52; F55; O20; O44; Q01; Q57; 330; competition; sustainability; development; Europe dependency; planetary boundaries